ANALISIS JENIS WASEI EIGO DI MEDIA SOSIAL TWITTER - Anggi Prahesta Hermawan; Firdhan Raka Iryananda; Arianty Visiaty (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2018)
In this era, the internet had a mass effect on the society that causes communication behavior between person changed, especially communication in social media. Communicate in social media tend to be freer and has no boundaries that give a role to form a newborn vocabulary. But, each of social media has different character and feature, one of them is character limit on Twitter. This research focused on wasei eigo forming and use in Twitter. This paper used a qualitative descriptive method to analyze content. First, gathering data from native Japanese social media account by random searching. Second, data analysis by comparing data and theory. Third, the conclusion from the research. The purpose of this research is to understand the forming and use of wasei eigo in Twitter. The result of this research are: 1) Not all wasei eigo can be categorized in theory that written by Tanabe (1989), 2) Some of wasei eigo have the same meaning but has a different variation, 3) The other wasei eigo word has more than one type.